International Dermoscopy Society criteria for non‐neoplastic dermatoses (general dermatology): validation for skin of color through a Delphi expert consensus. (2nd July 2021) - Errichetti, Enzo; Ankad, Balachandra S.; Jha, Abhijeet K.; Sonthalia, Sidharth; Akay, Bengu N.; Bakos, Roberto; Bhat, Yasmeen J.; Bosseila, Manal; Braun, Ralph; Cabo, Horacio; Cohen Sabban, Emilia N.; Chatterjee, Manas; et al.
Abstract: Background: The International Dermoscopy Society (IDS) recently released a set of five basic dermoscopic parameters (vessels, scales, follicular findings, "other structures, " and specific clues) encompassing a total of 31 subitems to standardize the use of dermoscopy in non‐neoplastic dermatoses, yet they have been developed taking into account Caucasian/Asian skin, with consequent possible limitations if used in dark skin. Objectives: To validate the abovementioned criteria for the use in dark‐skinned patients (phototypes IV–VI) through an expert consensus. Methods: The two‐round Delphi method was adopted, with an iterative process consisting of two rounds of email questionnaires. Potential panelists were recruited via e‐mail from all over the world based on their expertise on dermoscopy of non‐neoplastic dermatoses in skin of color. Results: Twenty‐two panelists took part in the validation process. All of the five originally proposed parameters and subitems reached agreement during the first round, aside from "follicular red dots." Additionally, during round 1, five new subitems were proposed (perifollicular scales distribution, follicular openings obliteration, broken hairs, eccrine pigmentation, and eccrine ostia obliteration), along with the possibility to change the denomination of parameter 3 (from "follicular findings" to "follicular/eccrine findings") and split it into two subparameters ("follicular findings" and "eccrine findings"). All such proposals reached agreement during the second round and therefore were included in the final list, for a total of 37 items. Conclusions: Although nearly all the dermoscopic criteria originally proposed by the IDS are applicable even to darker phototypes, several additional variables need to be assessed.